Using a temporary emigration model to estimate abundance of stream fishes from hybrid removal surveys with and without block nets - Brock M. Huntsman; Russell W. Perry; Kai Palenscar; Brett Mills; Kerwin Russell; Marissa Wulff; Heather Dyer; Russell Barabe (Fisheries Research, 2026)

Assessing Recovery: Examination of Greenhouse Gas Fluxes, Soil Characteristics, and Vegetation in Sediment Enhanced Marshes - Danielle C. Perry; Nia Bartolucci; Cathleen Wigand; Kenneth B. Raposa; Joseph Loffredo; Wenley Ferguson; Robinson W. Fulweiler (Estuaries and Coasts, 2026)

Native‐Alien Dichotomy in Pathogen Genomics: Host Specialization Versus Environmental Decoupling - Yongning Li; George L. W. Perry; Mahajabeen Padamsee; Shixiao Yu (Ecology Letters, 2026)
Genome size is a key genomic trait underpinning evolutionary potential and ecological adaptation in pathogens, yet its biogeographic patterns remain poorly understood. From New Zealand data, we quantify the influence of host traits versus environmental factors on biogeographic patterns of genome size in pathogenic fungi, and test whether these predictors differ between native and alien pathogens. Host plants were the strongest predictors of genome size, with effects particularly pronounced in Basidiomycota and biotrophic fungi. Within co‐origin host–pathogen pairs (native–native; alien–alien), conservative host traits were associated with smaller pathogen genomes overall, but with larger genomes in Basidiomycota. Host effects were stronger in native pathogens, while environmental filtering diverged, with climate dominating in native pathogens and terrain‐related factors in alien pathogens. Native pathogens exhibited pronounced geographic genomic differentiation, whereas alien pathogens showed spatial homogenization. These results reveal a hierarchical framework that enhances predictions of disease dynamics under global environmental change.

An Urban Taonga: The Distribution and Abundance of Tuna in Urban Streams Across Tāmaki Makaurau, Aotearoa‐New Zealand - Nicole A. Whitelock; Kevin S. Simon; George L. W. Perry (New Zealand Journal of Marine and Freshwater Research, 2026)
Freshwater eels of the Anguilla genus are experiencing global decline, largely driven by human activity. In Aotearoa‐New Zealand, tuna (both shortfin and longfin eels) are similarly affected, with habitat fragmentation and modification key drivers of their decline. We investigated the distribution and abundance of tuna across regional, catchment and reach‐level scales in an urban environment. We developed species distribution models (SDMs) across the Tāmaki Makaurau (Auckland) region to explore patterns in tuna distribution across an urbanisation gradient. Additionally, we conducted a field survey across an urban catchment in Tāmaki Makaurau to assess the local habitat features associated with tuna presence and abundance. The predictive power of our SDMs was limited, and the field survey revealed that tuna were broadly distributed throughout the urban catchment, displaying only weak associations with specific habitat features. These findings suggest that in the absence of movement barriers, tuna can occupy a wide range of habitats throughout urban streams. However, the presence of tuna may not indicate suitable habitat for survival and growth, as their robust and opportunistic nature allows them to persist even in suboptimal environments.

Who needs closure? Estimating abundance with a Markovian availability model for geographically open removal sampling - Russell W. Perry; Adam C. Pope; A. Noble Hendrix; Joseph E. Kirsch; Bryan G. Matthias; Michael J. Dodrill (Ecology, 2026)
Removal sampling is an important method for estimating abundance, but nearly all removal models assume closure during sampling. Yet, closure may be difficult to assume, evaluate, or enforce in many settings. To address situations where populations are geographically open between each removal sample, we incorporated a Markovian availability process into an N‐mixture model framework. This model relates local abundance available for sampling to a superpopulation through recruitment of new individuals to the sampling area. To test the model, we (1) conducted parameter identifiability analysis, (2) fit the model to removal data generated from a random walk movement model, and (3) analyzed a case study of empirical removal data. Parameters were increasingly identifiable as capture probability exceeded 0.25 and removal samples increased from 3 to 6. Abundance estimates were unbiased when parameters were identifiable, except for scenarios that simulated a behavioral response to sampling. For our case study, the model estimated negligible recruitment for benthic‐oriented fishes, indicating closure, but we found evidence against closure for juvenile Chinook salmon, a highly mobile species. Our removal model allows researchers to formally test closure assumptions, to estimate the degree of closure, and to estimate abundance without bias when closure is violated.

Restoring the wild east: Predicting public support for cougar and red wolf reintroduction in the eastern United States - Benjamin Ghasemi; Jeremy T. Bruskotter; John A. Vucetich; L. Mark Elbroch; Robyn S. Wilson; Neil H. Carter; Axel Moehrenschlager; Shelby Perry; Joseph W. Hinton (Biological Conservation, 2026)

Social and Ecological Context Shape Biological Invasions in Complex Landscapes - George L. W. Perry; James M. R. Brock; Cameron B. Guy; Casey Hamilton; Finnbar Lee; Dion L. Pou; Elizabeth Williams; Erica A. H. Smithwick (Current Landscape Ecology Reports, 2025)

Unique physiological and regulatory activity drives divergent toxin and non-toxin gene expression in rattlesnake accessory venom glands - Claire Kim; Sierra N. Smith; Siddharth S. Gopalan; Samuel R. Kerwin; Kaas Ballard; Blair W. Perry; Cara F. Smith; Anthony J. Saviola; Richard H. Adams; Stephen P. Mackessy; Todd A. Castoe (Toxicon, 2025)

Spinosyn resistance and cross-resistance – A 25 year review and analysis - Thomas C. Sparks; Frank J. Wessels; Trent Perry; Michael J. Price; Melissa W. Siebert; David G.J. Mann (Pesticide Biochemistry and Physiology, 2025)

Disentangling a genome-wide mosaic of conflicting phylogenetic signals in Western Rattlesnakes - Justin M. Bernstein; Yannick Z. Francioli; Drew R. Schield; Richard H. Adams; Blair W. Perry; Keaka Farleigh; Cara F. Smith; Jesse M. Meik; Stephen P. Mackessy; Todd A. Castoe (Molecular Phylogenetics and Evolution, 2025)

Survival, Travel Time, and Use of Migration Routes by Juvenile Steelhead in a Modified River Estuary - Adam C. Pope; Russell W. Perry; Dalton J. Hance; Rebecca A. Buchanan (Estuaries and Coasts, 2025)

Leaf Dry Matter Content Is Phylogenetically Conserved and Related to Environmental Conditions, Especially Wildfire Activity - Dachuan Dai; Dongli Yu; Wuchao Gao; George L. W. Perry; Adrian M. Paterson; Chengming You; Shixing Zhou; Zhenfeng Xu; Congde Huang; Dongyu Cao; Timothy J. Curran; Xinglei Cui (Ecology Letters, 2025)
Leaf dry matter content (LDMC) is an important determinant of plant flammability. Investigating global patterns of LDMC could provide insights into worldwide plant flammability patterns, informing wildfire management. We characterised global patterns of LDMC across 4074 species from 216 families, revealing that phylogenetic and environmental constraints influence LDMC. LDMC varied across growth forms and taxonomic groups, displaying phylogenetic niche conservatism. Temperature, precipitation, aridity index, soil total nitrogen content and wildfire activity affected LDMC, and the effect of wildfire activity was stronger than other environmental factors across species with postfire regeneration abilities. Such species had higher LDMC, and their LDMC was less phylogenetically conserved and more strongly associated with fire activity. Our results suggest that, although LDMC shows phylogenetic niche conservatism, LDMC is determined by environmental factors, especially wildfire activity. Wildfire has likely acted as a selective pressure towards high LDMC across species that persist through fire using postfire regeneration.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Back from the brink: Estimating daily and annual abundance of natural-origin salmon smolts from 30-years of mixed-origin capture-recapture data - Dalton J. Hance; John M. Plumb; Russell W. Perry; Kenneth F. Tiffan (Fisheries Research, 2024)

Producing 3D radargrams from orbital radar sounding data at Mars: History, results, methods, lessons and plans - Frederick J. Foss; Nathaniel E. Putzig; Bruce A. Campbell; Stewart A. Levin; Matthew R. Perry; John W. Holt; Michael S. Christoffersen; Isaac B. Smith; Gareth A. Morgan; Aaron T. Russell (Icarus, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Using parentage-based tagging to estimate survival of Chinook salmon fry in a large storage reservoir - Adam C. Pope; Tobias J. Kock; Russell W. Perry; Karen M. Cogliati; Kathleen G. O’Malley; Christina A. Murphy; Dalton J. Hance; Scott D. Fielding (Environmental Biology of Fishes, 2024)

Revealing the palaeoecology of silent taxa: selecting proxy species from associations in modern vegetation data - Jacqui M. M. Vanderhoorn; Janet M. Wilmshurst; Sarah J. Richardson; Thomas R. Etherington; George L. W. Perry (Journal of Biogeography, 2024)
Aim Species severely under‐represented in fossil pollen records leave gaps in interpretations and reconstructions of past vegetation. These ‘silent taxa’ leave little or no trace due to low pollen production, dispersal, preservation and taxonomic resolution. An approach for including them is through associating them with other species with reliable pollen representation. Here, we demonstrate a method for selecting such a proxy species for the Holocene using modern vegetation data. Location New Zealand. Taxon Beilschmiedia tawa (A.Cunn.) Benth. & Hook. F. ex Kirk (Lauraceae). Methods We used vegetation plot data to perform a pairwise co‐occurrence analysis of the New Zealand indigenous forest metacommunity to identify species with a strong positive association with Beilschmiedia tawa (tawa), a common tree severely under‐recorded in the pollen record. For those species, we then modelled their realised climatic niches to identify species with high niche overlap. We discuss how well those species could be interpreted from the Holocene fossil pollen record based on the representation of their pollen taxa. Results Knightia excelsa (rewarewa; Proteaceae) is a potential proxy for B. tawa in Holocene fossil pollen records, and other, range‐limited species may provide community‐specific proxies. We show combining resampling with sub‐sampling is a robust method for reducing the high false positive rate associated with large co‐occurrence analyses (1000+ sites) by limiting the sample size to 100 sites. Main Conclusions We show that the palaeoecology of silent taxa can be studied via proxy species, allowing their past distributions to be better understood. We highlight the importance of modelling many aspects of the realised niche to understand the usefulness and limitations of the silent–proxy association. Future research should focus on testing the underlying assumptions of the silent–proxy relationship so that models built on modern data can confidently be applied to palaeoecological data.

fNIRS is capable of distinguishing laterality of lower body contractions - Rob J. MacLennan; Jesus A. Hernandez-Sarabia; Shawn M. Reese; JoCarol E. Shields; Claire M. Smith; Katharina Stute; Jordyn Collyar; Alex A. Olmos; Tyler L. Danielson; Demi L. MacLennan; Jason I. Pagan; Ryan M. Girts; et al. (Experimental Brain Research, 2024)

A new multispectral index for canopy nitrogen concentration applicable across growth stages in ryegrass and barley - Manish Kumar Patel; Dongryeol Ryu; Andrew W. Western; Glenn J. Fitzgerald; Eileen M. Perry; Helen Suter; Iain M. Young (Precision Agriculture, 2024)
Accurately monitoring Canopy Nitrogen Concentration (CNC) is a prerequisite for precision nitrogen (N) fertiliser management at the farm scale with carbon and N budgeting across the landscape and ecosystems. While many spectral indices have been proposed for CNC monitoring, their applicability and accuracy are often adversely affected by confounding factors such as aboveground biomass (AGB), crop type, growth stages, and environmental conditions, limiting their broader application and adoption; with AGB being one of the most dominant signals and confounding factors at canopy scale. The confounding effect can become more challenging as AGB is also physiologically linked with CNC across the growth stages. Additionally, the interplay between index form, selection of optimal wavebands and their bandwidths remains poorly understood for CNC index design. This study proposes robust and cost-effective 2- and 4-waveband multispectral (MS) CNC indices applicable across a wide range of crop conditions. We collected 449 canopy reflectance spectra (400–980 nm) together with corresponding CNC and AGB measurements across four growth stages of ryegrass (winter and summer), and five growth stages of barley (winter-spring) in Victoria, Australia, in 2018 and 2019. All possible waveband (400–980 nm) combinations revealed that the best combination varied between seasons and crop types. However, the visible spectrum, particularly the blue region, presented high and consistent performance. Bandwidths of 10–40 nm outperformed either very narrow (2 nm) or very broad bandwidths (80 nm). The newly developed 2-waveband index (416 and 442 nm with 10-nm bandwidth; R 2 = 0.75 and NRMSE = 0.2) and 4-waveband index (512, 440, 414 and 588 nm with 40-nm bandwidth; R 2 = 0.81 and NRMSE = 0.17) exhibited the best performance, while validation with an independent dataset (from a different growing period to those used in the model development) obtained NRMSE values of 0.25 and 0.24, respectively. The 4-waveband index provides enhanced performance and permits use of broader bandwidths than its 2-waveband counterpart.

Global sensitivity analysis of APSIM-wheat yield predictions to model parameters and inputs - Shirui Hao; Dongryeol Ryu; Andrew W Western; Eileen Perry; Heye Bogena; Harrie Jan Hendricks Franssen (Ecological Modelling, 2024)

A cloudy forecast for species distribution models: Predictive uncertainties abound for California birds after a century of climate and land‐use change - John D. J. Clare; Perry de Valpine; Diana A. Moanga; Morgan W. Tingley; Steven R. Beissinger (Global Change Biology, 2024)
Correlative species distribution models are widely used to quantify past shifts in ranges or communities, and to predict future outcomes under ongoing global change. Practitioners confront a wide range of potentially plausible models for ecological dynamics, but most specific applications only consider a narrow set. Here, we clarify that certain model structures can embed restrictive assumptions about key sources of forecast uncertainty into an analysis. To evaluate forecast uncertainties and our ability to explain community change, we fit and compared 39 candidate multi‐ or joint species occupancy models to avian incidence data collected at 320 sites across California during the early 20th century and resurveyed a century later. We found massive (>20,000 LOOIC) differences in within‐time information criterion across models. Poorer fitting models omitting multivariate random effects predicted less variation in species richness changes and smaller contemporary communities, with considerable variation in predicted spatial patterns in richness changes across models. The top models suggested avian environmental associations changed across time, contemporary avian occupancy was influenced by previous site‐specific occupancy states, and that both latent site variables and species associations with these variables also varied over time. Collectively, our results recapitulate that simplified model assumptions not only impact predictive fit but may mask important sources of forecast uncertainty and mischaracterize the current state of system understanding when seeking to describe or project community responses to global change. We recommend that researchers seeking to make long‐term forecasts prioritize characterizing forecast uncertainty over seeking to present a single best guess. To do so reliably, we urge practitioners to employ models capable of characterizing the key sources of forecast uncertainty, where predictors, parameters and random effects may vary over time or further interact with previous occurrence states.

Circadian gene transcription plays a role in cellular metabolism in hibernating brown bears, Ursus arctos - Ellery P. Vincent; Blair W. Perry; Joanna L. Kelley; Charles T. Robbins; Heiko T. Jansen (Journal of Comparative Physiology B, 2023)

Drivers of shoreline change on Pacific coral reef islands: linking island change to processes - Meghna Sengupta; Murray R. Ford; Paul S. Kench; George L. W. Perry (Regional Environmental Change, 2023)
Reef islands are considered highly vulnerable to the impacts of anthropogenic climate change. While existing studies provide evidence of high dynamism and predominant stability over recent periods of sea-level rise, efforts to statistically link recorded morphological changes to processes are limited. We analyse shoreline changes across an expansive region of diverse oceanographic and climatic conditions and assess those observations relative to the processes potentially driving change. This record comprises 568 islands from 42 atolls spanning the western to the central Pacific Ocean from the Federated States of Micronesia, Marshall Islands, Kiribati and Tuvalu, and is one of the first robust attempts to statistically attribute the drivers of observed island changes within the past half-century. Our analyses demonstrate that island change and a range of its potential controls, including oceanographic, climatic and local-scale morphometric characteristics of reefs and islands, are not correlated, underscoring that no single variable could predict a uniform response across the study islands. The lack of association between sea-level rise and shoreline change on this large sample of islands addresses the common notion of a linear relationship between rising sea levels and magnitude of erosion in reef island systems. We emphasise the critical need to move from simplistic assessments of island change, highlight the importance of incorporating multiple predictors and the need for more computationally robust models.

Simulating the migration dynamics of juvenile salmonids through rivers and estuaries using a hydrodynamically driven enhanced particle tracking model - Vamsi Krishna Sridharan; Doug Jackson; Andrew M. Hein; Russell W. Perry; Adam C. Pope; Noble Hendrix; Eric M. Danner; Steven T. Lindley (Ecological Modelling, 2023)

Retrieving canopy nitrogen concentration and aboveground biomass with deep learning for ryegrass and barley: Comparing models and determining waveband contribution - Manish Kumar Patel; José Padarian; Andrew W. Western; Glenn J. Fitzgerald; Alex B. McBratney; Eileen M. Perry; Helen Suter; Dongryeol Ryu (Field Crops Research, 2023)

Seasonal differences in day-roost selection by Northern long-eared bats (Myotis septentrionalis) in Louisiana and a meta-analytical comparison across North America - Carlos J. Garcia; David A. Ray; Roger W. Perry; Richard D. Stevens (Forest Ecology and Management, 2023)

Quantifying the effects of tides, river flow, and barriers on movements of Chinook Salmon smolts at junctions in the Sacramento – San Joaquin River Delta using multistate models - Michael J. Dodrill; Russell W. Perry; Adam C. Pope; Xiaochun Wang (Environmental Biology of Fishes, 2022)

An Outlook for Deep Learning in Ecosystem Science - George L. W. Perry; Rupert Seidl; André M. Bellvé; Werner Rammer (Ecosystems, 2022)
Rapid advances in hardware and software, accompanied by public- and private-sector investment, have led to a new generation of data-driven computational tools. Recently, there has been a particular focus on deep learning—a class of machine learning algorithms that uses deep neural networks to identify patterns in large and heterogeneous datasets. These developments have been accompanied by both hype and scepticism by ecologists and others. This review describes the context in which deep learning methods have emerged, the deep learning methods most relevant to ecosystem ecologists, and some of the problem domains they have been applied to. Deep learning methods have high predictive performance in a range of ecological contexts, leveraging the large data resources now available. Furthermore, deep learning tools offer ecosystem ecologists new ways to learn about ecosystem dynamics. In particular, recent advances in interpretable machine learning and in developing hybrid approaches combining deep learning and mechanistic models provide a bridge between pure prediction and causal explanation. We conclude by looking at the opportunities that deep learning tools offer ecosystem ecologists and assess the challenges in interpretability that deep learning applications pose.

The impact of low nitrogen conditions on the chemical composition and flour pasting properties of quality protein maize - Schae-Lee Olckers; Garry Osthoff; Perry K. W. Ng; Angeline van Biljon; Maryke Labuschagne (Cereal Research Communications, 2022)

Degradation and recovery of alpine meadow catenas in the source zone of the Yellow River, Western China - Gary Brierley; Xi-lai Li; Kirstie Fryirs; Jay Gao; Yan Shi; George L. W. Perry; Carola Cullum (Journal of Mountain Science, 2022)

A Case Study of Large Floodplain River Restoration: Two Decades of Monitoring the Merwin Preserve and Lessons Learned through Water Level Fluctuations and Uncontrolled Reconnection to a Large River - Levi E. Solomon; Andrew F. Casper; Kristopher A. Maxson; James T. Lamer; Trent W. Ford; K. Douglass Blodgett; Tharran Hobson; Denim Perry; Nathan T. Grider; Rob B. Hilsabeck; Thad R. Cook; Kevin S. Irons; et al. (Wetlands, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

The Effect of Marsh Age on Ecosystem Function in a Rapidly Transgressing Marsh - Amy K. Langston; Daniel J. Coleman; Nathalie W. Jung; Justin L. Shawler; Alexander J. Smith; Bethany L. Williams; Serina S. Wittyngham; Randolph M. Chambers; James E. Perry; Matthew L. Kirwan (Ecosystems, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Vacant lot soil degradation and mowing frequency shape communities of belowground invertebrates and urban spontaneous vegetation - Kayla I. Perry; Nicole C. Hoekstra; Steve W. Culman; Mary M. Gardiner (Urban Ecosystems, 2021)

Harbor Seals as Sentinels of Ice Dynamics in Tidewater Glacier Fjords - Jamie N. Womble; Perry J. Williams; Robert W. McNabb; Anupma Prakash; Rudiger Gens; Benjamin S. Sedinger; Cheyenne R. Acevedo (Frontiers in Marine Science, 2021)
Tidewater glaciers calve icebergs into the marine environment which serve as pupping, molting, and resting habitat for some of the largest seasonal aggregations of harbor seals ( Phoca vitulina richardii ) in the world. Although they are naturally dynamic, advancing and retreating in response to local climatic and fjord conditions, most tidewater glaciers around the world are thinning and retreating. Climate change models predict continued loss of land-based ice with unknown impacts to organisms such as harbor seals that rely on glacier ice as habitat for critical life history events. To understand the impacts of changing ice availability on harbor seals, we quantified seasonal and annual changes in ice habitat in Johns Hopkins Inlet, a tidewater glacier fjord in Glacier Bay National Park in southeastern Alaska. We conducted systematic aerial photographic surveys ( n = 55) of seals and ice during the pupping (June; n = 30) and molting (August; n = 25) periods from 2007 to 2014. Object-based image analysis was used to quantify the availability and spatial distribution of floating ice in the fjord. Multivariate spatial models were developed for jointly modeling stage-structured seal location data and ice habitat. Across all years, there was consistently more ice in the fjord during the pupping season in June than during the molting season in August, which was likely driven by seasonal variation in physical processes that influence the calving dynamics of tidewater glaciers. Non-pup harbor seals and ice were correlated during the pupping season, but this correlation was reduced during the molting season suggesting that harbor seals may respond to changes in habitat differently depending upon trade-offs associated with life history events, such as pupping and molting, and energetic costs and constraints associated with the events.

Quantifying the base flow of the Colorado River: its importance in sustaining perennial flow in northern Arizona and southern Utah (USA) - Riley K. Swanson; Abraham E. Springer; David K. Kreamer; Benjamin W. Tobin; Denielle M. Perry (Hydrogeology Journal, 2021)

Stony Coral Tissue Loss Disease in Florida Is Associated With Disruption of Host–Zooxanthellae Physiology - Jan H. Landsberg; Yasunari Kiryu; Esther C. Peters; Patrick W. Wilson; Noretta Perry; Yvonne Waters; Kerry E. Maxwell; Lindsay K. Huebner; Thierry M. Work (Frontiers in Marine Science, 2020)
Samples from eight species of corals ( Colpophyllia natans , Dendrogyra cylindrus , Diploria labyrinthiformis , Meandrina meandrites , Montastraea cavernosa , Orbicella faveolata, Pseudodiploria strigosa , and Siderastrea siderea ) that exhibited gross clinical signs of acute, subacute, or chronic tissue loss attributed to stony coral tissue loss disease (SCTLD) were collected from the Florida Reef Tract during 2016–2018 and examined histopathologically. The hallmark microscopic lesion seen in all eight species was focal to multifocal lytic necrosis (LN) originating in the gastrodermis of the basal body wall (BBW) and extending to the calicodermis, with more advanced lesions involving the surface body wall. This was accompanied by other degenerative changes in host cells such as mucocyte hypertrophy, degradation and fragmentation of gastrodermal architecture, and disintegration of the mesoglea. Zooxanthellae manifested various changes including necrosis (cytoplasmic hypereosinophilia, pyknosis); peripheral nuclear chromatin condensation; cytoplasmic vacuolation accompanied by deformation, swelling, or atrophy; swollen accumulation bodies; prominent pyrenoids; and degraded chloroplasts. Polyhedral intracytoplasmic eosinophilic periodic acid–Schiff-positive crystalline inclusion bodies (∼1–10 μm in length) were seen only in M. cavernosa and P. strigosa BBW gastrodermis in or adjacent to active lesions and some unaffected areas (without surface lesions) of diseased colonies. Coccoidlike or coccobacilloidlike structures (Gram-neutral) reminiscent of microorganisms were occasionally associated with LN lesions or seen in apparently healthy tissue of diseased colonies along with various parasites and other bacteria all considered likely secondary colonizers. Of the 82 samples showing gross lesions of SCTLD, 71 (87%) were confirmed histologically to have LN. Collectively, pathology indicates that SCTLD is the result of a disruption of host–symbiont physiology with lesions originating in the BBW leading to detachment and sloughing of tissues from the skeleton. Future investigations could focus on identifying the cause and pathogenesis of this process.

Matrix-level co-occurrence metrics are sensitive to sampling grain: a case study in species-rich shrublands - G. L. W. Perry; Ben P. Miller; Byron B. Lamont; Neal J. Enright (Plant Ecology, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

A Comparison of Different Statistical Methods for Addressing Censored Left Data in Temporal Trends Analysis of Pyrethroids in a California Stream - Lenwood W. Hall; Elgin Perry; Ronald D. Anderson (Archives of Environmental Contamination and Toxicology, 2020)

Resolving marine dissolved organic phosphorus ( DOP ) composition in a coastal estuary - Douglas W. Bell; Perry J. Pellechia; Ellery D. Ingall; Claudia R. Benitez‐Nelson (Limnology and Oceanography, 2020)
A mechanistic understanding of dissolved organic phosphorus (DOP) utilization, and its role in the marine P cycle, requires knowledge of DOP molecular composition. In this study, a recently developed approach coupling electrodialysis and reverse osmosis with solution 31 P‐NMR analysis was used to examine DOP composition within a tidally dominated salt‐marsh estuary (North Inlet, South Carolina) over seasonal and tidal time frames. The isolation technique allowed for near complete recovery of the DOP pool (90% ± 13%; n = 12) with six broad compound classes quantified: phosphonates, phosphomonoesters, phosphodiesters, pyrophosphate, di‐ and tri‐phosphate nucleotides (nucleoP α ), and polyphosphate. Our results indicate that phosphomonoesters (ca. 61%) and phosphodiesters (ca. 31%) comprise the majority of the DOP pool, with relatively small contributions from pyrophosphates (ca. 4%), phosphonates (ca. 2%), nucleoP α (ca. 1%), and polyphosphates (ca. 1%). The study found no significant differences in DOP composition or concentration between tidal stages, despite significant tidal changes in dissolved organic nitrogen (DON):DOP stoichiometry. Significant seasonal variation was observed, with higher concentrations of phosphonates, nucleoP α , and monophosphates and lower phosphomonoester concentrations in Fall relative to all other seasons. We hypothesize that these seasonal variations reflect the balance between specific compound class seasonal production, lability, and local P demands associated with marine vs. terrestrial sources. Our results indicate that DOP composition exists at a dynamic equilibrium that is strongly conserved across diverse marine environments.

Side-Population Trophoblasts Exhibit the Differentiation Potential of a Trophoblast Stem Cell Population, Persist to Term, and are Reduced in Fetal Growth Restriction - Teena KJB Gamage; Jasper J Perry; Vicky Fan; Katie Groom; Lawrence W Chamley; Joanna L James (Stem Cell Reviews and Reports, 2020)

The role of psychology in determining human–predator conflict across southern Kenya - Laura R. Perry; Tom P. Moorhouse; Andrew J. Loveridge; David W. Macdonald (Conservation Biology, 2020)
Conflict between people and carnivores can lead to the widespread killing of predators in retaliation for livestock loss and is a major threat to predator populations. In Kenya, a large, rural, pastoralist population comes into regular conflict with predators, which persist across southern Kenya. We explored the social and psychological backdrop to livestock management practices in this area in a process designed to be easy to use and suitable for use across large areas for the study of conflict and transboundary implementation of wildlife conflict reduction measures, focusing on community involvement and needs. We carried out fully structured interviews of livestock managers with a survey tool that examined how social and psychological factors may influence livestock management behavior. We compared survey responses on 3 sites across the study area, resulting in 723 usable responses. Efficacy of individuals’ livestock management varied between and within communities. This variation was partially explained by normative and control beliefs regarding livestock management. Individual livestock managers’ self‐reported management issues were often an accurate reflection of their practical management difficulties. Psychological norms, control beliefs, and attitudes differed among sites, and these differences partially explained patterns associated with conflict (i.e., variation in livestock management behavior). Thus, we conclude that a one‐size‐fits‐all approach to improving livestock management and reducing human–predator conflict is not suitable.

Coral Reefs of Abu Dhabi, United Arab Emirates: Analysis of Management Approaches in Light of International Best Practices and a Changing Climate - Haïfa Ben-Romdhane; Rima W. Jabado; Edwin Mark Grandcourt; Richard John Obrien Perry; Ayesha Yousef Al Blooshi; Prashanth Reddy Marpu; Taha B. M. J. Ouarda; Hosni Ghedira (Frontiers in Marine Science, 2020)

Trait matching and phenological overlap increase the spatio‐temporal stability and functionality of plant–pollinator interactions - Guadalupe Peralta; Diego P. Vázquez; Natacha P. Chacoff; Silvia B. Lomáscolo; George L. W. Perry; Jason M. Tylianakis (Ecology Letters, 2020)
Morphology and phenology influence plant–pollinator network structure, but whether they generate more stable pairwise interactions with higher pollination success remains unknown. Here we evaluate the importance of morphological trait matching, phenological overlap and specialisation for the spatio‐temporal stability (measured as variability) of plant–pollinator interactions and for pollination success, while controlling for species' abundance. To this end, we combined a 6‐year plant–pollinator interaction dataset, with information on species traits, phenologies, specialisation, abundance and pollination success, into structural equation models. Interactions among abundant plants and pollinators with well‐matched traits and phenologies formed the stable and functional backbone of the pollination network, whereas poorly matched interactions were variable in time and had lower pollination success. We conclude that phenological overlap could be more useful for predicting changes in species interactions than species abundances, and that non‐random extinction of species with well‐matched traits could decrease the stability of interactions within communities and reduce their functioning.

Site use and connectivity of female grey seals (Halichoerus grypus) around Wales - Izzy Langley; Tobias Rosas da Costa Oliver; Lex Hiby; Thomas B. Stringell; Ceri W. Morris; Oliver O’Cadhla; Lisa Morgan; Kate Lock; Sarah Perry; Stephen Westcott; Dave Boyle; Birgitta I. Büche; et al. (Marine Biology, 2020)
Grey seals ( Halichoerus grypus ) are a qualifying feature of three special areas of conservation (SACs) in Wales, yet relatively little is known of their site use along this coastline. Since 1992, many individuals and organisations have contributed to a grey seal photographic identification database held by Natural Resources Wales, which is one of the largest and oldest of its kind, providing key information from grey seal haul-out sites around the Celtic and Irish Seas. Here, we investigated spatial connectivity of haul-out sites and fidelity of adult females to breeding sites. The minimum number of adult female grey seals using the area between 1992 and 2016 was 2688. Individual capture histories and relative spatial transition probabilities ( P ij ) between pairs of location groups were calculated. Adjacent locations were highly connected (e.g. Lleyn Peninsula and Bardsey, P ij = 0.7) but connections spanned the entire region, up to 230 km apart (e.g. Skomer and Dee Estuary, P ij = 0.004). Resights were recorded within SACs (e.g. Lleyn Peninsula and Bardsey [Lleyn Peninsula and the Sarnau SAC], P ij = 0.7), between SACs (e.g. Bardsey and Skomer [Pembrokeshire Marine], P ij = 0.03), between SACs and non-designated areas (e.g. Skerries and Bardsey, P ij = 0.09) and between sites outside any protected area (e.g. Dee Estuary and Anglesey, P ij = 0.5). While inter-annual fidelity to breeding sites was high ( P ij = 0.82–1), individual female grey seals moved throughout the region. This evidence of extensive site use beyond protected areas is important for the management and conservation of grey seals around Wales.

Determining the underlying structure of insular isolation measures - Zachary T. Carter; George L. W. Perry; James C. Russell (Journal of Biogeography, 2020)
Aim Island isolation is measured in many ways. We seek to determine what the underlying latent factors characterizing these measures are, in order to understand how they mechanistically drive island biogeographical patterns and in order to recommend the most parsimonious measures. We then test the discriminatory power of the identified components against hypotheses generated from the biogeographical patterns of invasive rats. Location The 890 offshore islands (≥1 hectare area) of the New Zealand archipelago (latitude: 34.1–47.3°S, longitude: 166.2–178.4°E). Taxon Mammals. Methods We identified 16 measures that have been frequently used to characterize isolation in the past, including Euclidean‐based distance metrics, landscape connectivity metrics derived from least‐cost and circuit theory modelling, landscape buffers, stepping stones and insular area. We used principal components analysis (PCA) to synthesize the underlying structure of insular isolation with respect to terrestrial mammal dispersal. Finally, we tested the discriminatory power of retained principal components (PCs) using permutational multivariate analyses of variance (PERMANOVA). Tests include comparison of historical rat distributions, islands targeted for rat eradication and islands reinvaded by rats. Results The underlying structure of island isolation as characterized in the 16 metrics was described by three independent PCA components. Variable clustering suggests that PC1 captured distance from the mainland source to the focal island (PC1 Distance), PC2 described stepping stones available along the dispersal pathway (PC2 Stepping Stones) and PC3 described the focal island's position in the landscape (PC3 Insular Network). Each discriminatory test affirmed its respective biogeographical pattern hypothesis. Main conclusions The three underlying components we identify form the basis of a robust description of insular isolation that is of broad importance to understanding island biogeography dynamics. Moreover, these components can be applied across taxa without extensive structural or functional assumptions because the highest loading variables are not biologically informed.

Prevalence of Eight Phthalate Monoesters in Water from the Okavango Delta, Northern Botswana - Perry W. Bartsch; Thea M. Edwards; John W. Brock (Bulletin of Environmental Contamination and Toxicology, 2019)

Developing a Social–Ecological–Environmental System Framework to Address Climate Change Impacts in the North Pacific - Steven J. Bograd; Sukyung Kang; Emanuele Di Lorenzo; Toyomitsu Horii; Oleg N. Katugin; Jackie R. King; Vyacheslav B. Lobanov; Mitsutaku Makino; Guangshui Na; R. Ian Perry; Fangli Qiao; Ryan R. Rykaczewski; et al. (Frontiers in Marine Science, 2019)

The role of reforestation in carbon sequestration - L. E. Nave; B. F. Walters; K. L. Hofmeister; C. H. Perry; U. Mishra; G. M. Domke; C. W. Swanston (New Forests, 2019)

Winter climate variability in the southern Appalachian Mountains, 1910–2017 - Montana A. Eck; L. Baker Perry; Peter T. Soulé; Johnathan W. Sugg; Douglas K. Miller (International Journal of Climatology, 2019)
Located in the mid‐latitudes and exhibiting the greatest topographic relief in the eastern United States, the southern Appalachian Mountains (SAM) contain some of the most diverse climatological environments in the United States. This diversity is most pronounced in the winter season when temperature and snowfall can vary drastically across the region. In this study, we identify long‐term trends and variation of temperature and snowfall in the SAM of the southeastern United States during climatological winter (DJF) from 1910 to 2017. Along with recognizing statistically significant climatic trends, we also identify the influence of several teleconnection patterns, namely the El Niño‐Southern Oscillation (ENSO), North Atlantic Oscillation (NAO), and Pacific Decadal Oscillation (PDO) that further scientific understanding of how this region has remained a climatic anomaly. Results of this study indicate the SAM have experienced a statistically significant long‐term cooling trend since the early 20th century, with recent decades suggesting a reversal towards a warming pattern. Snowfall exhibited high interannual variability, with the 1960s and 1970s producing anomalously high amounts of snowfall. Several atmospheric forcing couplings are identified that align with anomalous conditions in the region. Most notably, negative temperature anomalies and higher snowfall amounts were frequently found during El Niño and negative NAO seasons, with the opposite being true during La Niña and positive NAO winters. The influence of these teleconnection patterns was spatially dependent, with lower elevations and eastern‐facing slopes being highly dependent on the phase of ENSO for snowfall, whereas higher elevations and western‐facing slopes were more reliant on the NAO. The identification of pattern couplings is critical to improving understanding of the anomalous climate of the SAM, enhancing seasonal forecasting, and predicting future climate change in the region.

Novel ecological and climatic conditions drive rapid adaptation in invasive Florida Burmese pythons - Daren C. Card; Blair W. Perry; Richard H. Adams; Drew R. Schield; Acacia S. Young; Audra L. Andrew; Tereza Jezkova; Giulia I.M. Pasquesi; Nicole R. Hales; Matthew R. Walsh; Michael R. Rochford; Frank J. Mazzotti; et al. (Molecular Ecology, 2018)
Invasive species provide powerful in situ experimental systems for studying evolution in response to selective pressures in novel habitats. While research has shown that phenotypic evolution can occur rapidly in nature, few examples exist of genomewide adaptation on short “ecological” timescales. Burmese pythons ( Python molurus bivittatus ) have become a successful and impactful invasive species in Florida over the last 30 years despite major freeze events that caused high python mortality. We sampled Florida Burmese pythons before and after a major freeze event in 2010 and found evidence for directional selection in genomic regions enriched for genes associated with thermosensation, behaviour and physiology. Several of these genes are linked to regenerative organ growth, an adaptive response that modulates organ size and function with feeding and fasting in pythons. Independent histological and functional genomic data sets provide additional layers of support for a contemporary shift in invasive Burmese python physiology. In the Florida population, a shift towards maintaining an active digestive system may be driven by the fitness benefits of maintaining higher metabolic rates and body temperature during freeze events. Our results suggest that a synergistic interaction between ecological and climatic selection pressures has driven adaptation in Florida Burmese pythons, demonstrating the often‐overlooked potential of rapid adaptation to influence the success of invasive species.

Nitrogen isotope (δ 15 N) patterns for amino acids in lemur bones are inconsistent with aridity driving megafaunal extinction in south‐western Madagascar - Sean W. Hixon; Emma A. Elliott Smith; Brooke E. Crowley; George H. Perry; Jeannot Randrianasy; Jean Freddy Ranaivoarisoa; Douglas J. Kennett; Seth D. Newsome (Journal of Quaternary Science, 2018)
Most endemic species with body masses >10 kg on Madagascar went extinct within the past 1000 years. The extent to which human predation, anthropogenic landscape transformation and aridification may separately or together explain this extinction pattern remains controversial. We present nitrogen isotope (δ 15 N) values of individual amino acids preserved in bones from now‐extinct Pachylemur insignis and extant Propithecus verreauxi from two subfossil sites in south‐western Madagascar: Tsirave and Taolambiby. The amino acid‐specific approach allows us to identify environmental signals that are otherwise difficult to recognize in bulk collagen δ 15 N values. Specifically, we use the δ 15 N values of source amino acids (phenylalanine and lysine) as a proxy for habitat aridity between ca . 4000 years ago and present and the spacing of δ 15 N values between trophic and source amino acids to quantify trophic levels for these two lemur species. Despite paleoenvironmental evidence for lowering water tables and the expansion of relatively arid savanna between 4000 and 1000 years ago, our isotope data suggest that these lemurs did not live in increasingly arid habitats and did not change their trophic level. Together, our results support the hypothesis that aridity alone did not play a major role in late Holocene megafaunal extinctions in south‐western Madagascar.

Shoot-Level Flammability of Species Mixtures is Driven by the Most Flammable Species: Implications for Vegetation-Fire Feedbacks Favouring Invasive Species - Sarah V. Wyse; George L. W. Perry; Timothy J. Curran (Ecosystems, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Does heating stimulate germination in Leptospermum scoparium (mānuka; Myrtaceae)? - Paul F. Battersby; Janet M. Wilmshurst; Timothy J. Curran; George L. W. Perry (New Zealand Journal of Botany, 2017)
Fire regimes are powerful selective filters. In New Zealand, fire activity was rare before human settlement, and New Zealand’s indigenous woody flora shows little adaptation to frequent fire. One of the few woody indigenous species to show adaptation to frequent fire is Leptospermum scoparium (Myrtaceae), a Plio‐Pleistocene immigrant from Australia. Leptospermum scoparium is a widespread early‐successional shrub to small tree that frequently dominates post‐fire successions, and shows geographically‐variable pyriscent serotiny, a fire‐adaptation in which seeds are retained in the canopy and open post‐fire. Another widespread reproductive adaptation to fire is heat‐stimulated germination. Some Australian Leptospermum respond positively to heat treatment, and observations in New Zealand suggest that the seeds of L. scoparium within thick‐walled capsules open immediately after fire and successfully germinate, indicating at least no deleterious effect of heating. In some fire‐prone systems such as Mediterranean shrublands, traits such as serotiny and heat‐stimulated germination have been positively associated with traits associated with flammability (e.g. retention of dead fuel). Here we evaluate the effect of heat stimulation (short exposure to high temperatures) of capsules on germination in L. scoparium from New Zealand, and evaluate links between germination, serotiny and shoot‐level flammability. Germination trials using seed collected from 12 populations indicated no consistent positive or negative effect of heat treatment on germination success (germinability). These trials suggest that the capsules of L. scoparium at least provide adequate insulation to heating. Germinability was not consistently related to either serotiny or flammability; nor was it related to latitude or elevation. While taxa from other fire‐prone ecosystems may show coordinated trait responses to fire, the lack of association between physical measures of flammability and germination rates indicate that this is not the case in L. scoparium , New Zealand’s most fire‐adapted indigenous woody species.

Soil or fire: what causes treeless sedgelands in Tasmanian wet forests? - David M. J. S. Bowman; George L. W. Perry (Plant and Soil, 2017)

Increased alertness, better than posture prioritization, explains dual-task performance in prosthesis users and controls under increasing postural and cognitive challenge - Charla L. Howard; Bonnie Perry; John W. Chow; Chris Wallace; Dobrivoje S. Stokic (Experimental Brain Research, 2017)

Methyl isonicotinate — a non-pheromone thrips semiochemical — and its potential for pest management - D. A. J. Teulon; M. M. Davidson; N. B. Perry; M. -C. Nielsen; C. Castañé; D. Bosch; J. Riudavets; R. W. H. M. van Tol; W. J. de Kogel (International Journal of Tropical Insect Science, 2017)

Size‐based fruit selection by a keystone avian frugivore and effects on seed viability - Andrew Paul McKenzie Pegman; George L. W. Perry; Mick N. Clout (New Zealand Journal of Botany, 2017)
The non‐random selection of fruits by frugivores can affect plant demography by changing the probability of seedling recruitment. We investigated whether the New Zealand pigeon ( Hemiphaga novaeseelandiae ) exhibits size‐based preference of fruit in two indigenous tree species, Vitex lucens and Prumnopitys ferruginea , that have large fleshy diaspores containing single seeds. We also assessed if there was an advantage for seeds that were actively dispersed since birds may select fruits that have viable seeds (although the cue for such selection remains unclear) and whether a combined scarification–deinhibition advantage was conferred on germination due to seed passage through the gut. Using seed length as a proxy for fruit size, we compared the length of passively dispersed fruits in traps with the estimated fruit length of actively dispersed seeds in six trees of each species across three areas in one fruiting season. For both species, actively dispersed seeds were significantly longer than seeds from passively dispersed fruit, suggesting frugivore preference for larger fruit. Seeds from passively dispersed P. ferruginea fruit had significantly higher viability than actively dispersed seeds and there was no measurable scarification–deinhibition effect. For V. lucens , there was no significant difference in viability between actively and passively dispersed seeds and there was a total lack of seed germination in our trial. Our results show a significant preference by H. novaeseelandiae for larger fruit in both tree species, which was possibly associated with annual fruit production since P. ferruginea trees that had more fruit produced larger fruit on average. That H. novaeseelandiae selected longer fruit in our study is consistent with the prediction that birds will prefer larger fruit when beak gape limitation is absent. However, active dispersal of larger seeds may not always be advantageous since passively dispersed intact fruit germinated equally well and may even have had a viability advantage.

Exploring fire adaptation in a land with little fire: serotiny in Leptospermum scoparium (Myrtaceae) - Paul F. Battersby; Janet M. Wilmshurst; Timothy J. Curran; Matthew S. McGlone; George L. W. Perry (Journal of Biogeography, 2017)
Aim Immigrant floras often have distinctive traits, well suited to the host region but absent from the autochthonous flora. An example is serotiny in the New Zealand ( NZ ) small tree, Leptospermum scoparium (Myrtaceae) belonging to a strongly fire‐adapted Australian clade. Serotiny in L. scoparium has been attributed either to strong selection by fire since human settlement, or taken as evidence that pre‐human fire in NZ was more important than assumed. By integrating field data, experimental analyses and long‐term fire histories, we sought to explain the spatial pattern of serotiny in L. scoparium in NZ , and evaluate these two explanations. Location New Zealand. Methods We quantified the distribution of serotiny in L. scoparium by analysing 137 populations distributed across NZ (two previous studies and ours), including 31 with Holocene fire histories. We assessed the relationship of serotiny with a suite of fire and climate environmental predictors, and between serotiny and shoot‐level flammability. Results Serotiny was strongly positively associated with latitude (more in the north), lower rainfall and higher temperatures. Serotinous populations were rare at sites with no history of fire. Serotiny was most prevalent in northern wetlands, where fire was recurrent during the Holocene, but was nearly absent from the southwestern Southern Alps. Shoot‐level flammability and serotiny were not correlated. Main conclusions The distribution of serotiny in L. scoparium relates not only to current environments but also to the legacy of regional shifts in vegetation during Quaternary glacial–interglacial cycles. Serotiny was maintained where the landscape experienced sporadic fire, but it is absent from NZ 's southern South Island because the sparse, open vegetation during the glacials did not support fire. Serotinous L. scoparium populations were therefore more common in the northern North Island. Human transformation of the fire regime over the last 750 years has likely favoured the spread of serotinous populations.

Characterizing Movement of Ground-Dwelling Arthropods with a Novel Mark-Capture Method Using Fluorescent Powder - Kayla I. Perry; Kimberly F. Wallin; John W. Wenzel; Daniel A. Herms (Journal of Insect Behavior, 2017)

Positive Feedbacks to Fire-Driven Deforestation Following Human Colonization of the South Island of New Zealand - Alan J. Tepley; Thomas T. Veblen; George L. W. Perry; Glenn H. Stewart; Cameron E. Naficy (Ecosystems, 2016)

Linking innovative measurement technologies (ConMon and Dataflow© systems) for high-resolution temporal and spatial dissolved oxygen criteria assessment - C. A. O’Leary; E. Perry; A. Bayard; L. Wainger; W. R. Boynton (Environmental Monitoring and Assessment, 2016)

Long-Term Trends of Nutrients and Phytoplankton in Chesapeake Bay - L. W. Harding; C. L. Gallegos; E. S. Perry; W. D. Miller; J. E. Adolf; M. E. Mallonee; H. W. Paerl (Estuaries and Coasts, 2016)

An emerging role for gasotransmitters in the control of breathing and ionic regulation in fish - Steve Perry; Y. Kumai; C. S. Porteus; V. Tzaneva; R. W. M. Kwong (Journal of Comparative Physiology B, 2016)

Amphetamine increases activity but not exploration in humans and mice - Arpi Minassian; Jared W. Young; Zackary A. Cope; Brook L. Henry; Mark A. Geyer; William Perry (Psychopharmacology, 2016)

Exotic Mammals and Invasive Plants Alter Fire-Related Thresholds in Southern Temperate Forested Landscapes - George L. W. Perry; Janet M. Wilmshurst; John Ogden; Neal J. Enright (Ecosystems, 2015)

Confirmation of delayed canopy wilting QTLs from multiple soybean mapping populations - Sadal Hwang; C. Andy King; Jeffery D. Ray; Perry B. Cregan; Pengyin Chen; Thomas E. Carter; Zenglu Li; Hussein Abdel-Haleem; Kevin W. Matson; William Schapaugh; Larry C. Purcell (Theoretical and Applied Genetics, 2015)

Hydrogen sulfide inhibits Na+ uptake in larval zebrafish, Danio rerio - Yusuke Kumai; Cosima S. Porteus; Raymond W. M. Kwong; Steve F. Perry (Pflügers Archiv - European Journal of Physiology, 2015)

A role for transcription factor glial cell missing 2 in Ca2+ homeostasis in zebrafish, Danio rerio - Yusuke Kumai; Raymond W. M. Kwong; Steve F. Perry (Pflügers Archiv - European Journal of Physiology, 2015)

Evaluation of a new chromogenic medium, chromID OXA-48, for recovery of carbapenemase-producing Enterobacteriaceae from patients at a university hospital in Turkey - P. Zarakolu; K. M. Day; H. E. Sidjabat; W. Kamolvit; C. V. Lanyon; S. P. Cummings; D. L. Paterson; M. Akova; J. D. Perry (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Capsaicin induces apoptosis in human small cell lung cancer via the TRPV6 receptor and the calpain pathway - Jamie K. Lau; Kathleen C. Brown; Aaron M. Dom; Theodore R. Witte; Brent A. Thornhill; Clayton M. Crabtree; Haley E. Perry; J. Michael Brown; John G. Ball; Rebecca G. Creel; C. Luke Damron; William D. Rollyson; et al. (Apoptosis, 2014)

Mapping the low palmitate fap1 mutation and validation of its effects in soybean oil and agronomic traits in three soybean populations - Andrea J. Cardinal; Rebecca Whetten; Sanbao Wang; Jérôme Auclair; David Hyten; Perry Cregan; Eleni Bachlava; Jason Gillman; Martha Ramirez; Ralph Dewey; Greg Upchurch; Lilian Miranda; et al. (Theoretical and Applied Genetics, 2014)

Inheritance of soybean aphid resistance in 21 soybean plant introductions - Carolyn M. Fox; Ki-Seung Kim; Perry B. Cregan; Curtis B. Hill; Glen L. Hartman; Brian W. Diers (Theoretical and Applied Genetics, 2014)

Scientific Bases for Numerical Chlorophyll Criteria in Chesapeake Bay - L. W. Harding; R. A. Batiuk; T. R. Fisher; C. L. Gallegos; T. C. Malone; W. D. Miller; M. R. Mulholland; H. W. Paerl; E. S. Perry; P. Tango (Estuaries and Coasts, 2014)

Restoration prospects for Heitutan degraded grassland in the Sanjiangyuan - Xi-lai Li; George L. W. Perry; Gary Brierley; Jay Gao; Jing Zhang; Yuan-wu Yang (Journal of Mountain Science, 2013)
In many ecosystems ungulates have coexisted with grasslands over long periods of time. However, high densities of grazing animals may change the floristic and structural characteristics of vegetation, reduce biodiversity, and increase soil erosion, potentially triggering abrupt and rapid changes in ecosystem condition. Alternate stable state theory provides a framework for understanding this type of dynamic. In the Sanjiangyuan atop the Qinghai-Tibetan plateau (QTP), grassland degradation has been accompanied by irruptions of native burrowing animals, which has accentuated the loss of ground cover. Severely degraded areas of alpine meadows are referred to as ‘Heitutan’. Here, using the framework of alternate stable state theory, we describe the proximate and ultimate drivers of the formation of Heitutan on the QTP, and we assess prospects for recovery, in relation to the degree of biophysical alteration, of these alpine meadows. Effective rehabilitation measures must address the underlying causes of degradation rather than their symptoms. Heitutan degradation is not uni-causal. Rather it reflects different mechanisms operating at different spatio-temporal scales across this vast region. Underlying causes include overly aggressive exploitation of the grasslands (e.g. overgrazing), amplification of grazing and erosion damage by small mammals when outbreaks occur, and/or climate change. Given marked variability in environmental conditions and stressors, restorative efforts must vary across the region. Restoration efforts are likely to yield greatest success if moderately and severely degraded areas are targeted as the first priority in management programmes, before these areas are transformed into extreme Heitutan.

A conceptual framework for predicting temperate ecosystem sensitivity to human impacts on fire regimes - D. B. McWethy; P. E. Higuera; C. Whitlock; T. T. Veblen; D. M. J. S. Bowman; G. J. Cary; S. G. Haberle; R. E. Keane; B. D. Maxwell; M. S. McGlone; G. L. W. Perry; J. M. Wilmshurst; et al. (Global Ecology and Biogeography, 2013)
Aim The increased incidence of large fires around much of the world in recent decades raises questions about human and non‐human drivers of fire and the likelihood of increased fire activity in the future. The purpose of this paper is to outline a conceptual framework for examining where human‐set fires and feedbacks are likely to be most pronounced in temperate forests world‐wide and to establish and test a methodology for evaluating this framework using palaeoecological records. Location T asmania, north‐western USA , southern S outh A merica and N ew Z ealand. Methods We outline a conceptual framework for predicting the sensitivity of ecosystems to human impacts on fire regimes and then use a circum‐ P acific comparison of existing historical reconstructions of fire, climate, human settlement and vegetation to evaluate this approach. Results Previous research investigating important controls on fire activity shows that the sensitivity of temperate ecosystems to human‐set fires is modulated by the frequency of natural fire occurrence, fuel moisture and fuel type and availability. Palaeoecological data from four temperate regions suggest that the effects of anthropogenic burning are greatest where fire is naturally rare, vegetation is poorly adapted to fire and fuel biomass is abundant and contiguous. Alternatively, where fire activity is naturally high and vegetation is well adapted to fire, evidence of human influence on fire and vegetation is less obvious. Main conclusions Palaeofire records suggest that the most dynamic and persistent ecosystem transitions occur where human activities increase landscape flammability through fire–vegetation feedbacks. Rapid forest transitions in biomass‐rich ecosystems such as N ew Z ealand and areas of Tasmania and southern South America illustrate how landscapes experiencing few fires can shift past tipping points to become fire‐prone landscapes with new alternative stable state communities. Comparisons of palaeoecological data from different regions with similar biophysical gradients but different human settlement histories can provide new opportunities for understanding ecosystem vulnerability to fire–climate–human interactions.

Adjusting survival estimates for premature transmitter failure: a case study from the Sacramento-San Joaquin Delta - Christopher M. Holbrook; Russell W. Perry; Patricia L. Brandes; Noah S. Adams (Environmental Biology of Fishes, 2013)

Sensitivity of survival to migration routes used by juvenile Chinook salmon to negotiate the Sacramento-San Joaquin River Delta - Russell W. Perry; Patricia L. Brandes; Jon R. Burau; A. Peter Klimley; Bruce MacFarlane; Cyril Michel; John R. Skalski (Environmental Biology of Fishes, 2013)

Evidence for a role of tight junctions in regulating sodium permeability in zebrafish (Danio rerio) acclimated to ion-poor water - Raymond W. M. Kwong; Yusuke Kumai; Steve F. Perry (Journal of Comparative Physiology B, 2013)

Reconstructing spatial vulnerability to forest loss by fire in pre‐historic New Zealand - George L. W. Perry; Janet M. Wilmshurst; Matt S. McGlone; Aaron Napier (Global Ecology and Biogeography, 2012)
Aim Despite small and transient populations, early Māori transformed large areas of New Zealand's forest landscapes. We sought to isolate the biophysical predictors that explain forest loss in the pre‐historic (i.e. pre‐European) period in New Zealand. Location New Zealand. Methods We used resampled boosted regression trees to isolate the key predictors of forest loss from a suite of 19 topographic, climatic, soil‐related and archaeological predictors at a 1‐km spatial resolution across New Zealand. Results The key predictors of fire‐driven forest loss during New Zealand's pre‐history relate to moisture and elevation gradients, with sites characterized by low moisture levels and gentle slopes being most vulnerable. Proxies for human activity were important in the North Island, where Māori population densities were higher, but not the South Island. The predicted pattern of forest loss and its relationship with biophysical variables suggest that early Māori neither deliberately protected fire‐prone regions nor systematically burnt less fire‐prone ones. Main conclusions Before Māori settlement of New Zealand fire was naturally rare, despite biophysical conditions being conducive to fire spread. The introduction of an ignition source by humans made widespread forest loss inevitable, even in the absence of sustained and deliberate use of fire. Rapid forest loss at the time of human settlement is recurrent across eastern Polynesia, so understanding this dynamic in New Zealand has implications for the region as a whole.

Follicular determinants of pregnancy establishment and maintenance - Ky G. Pohler; Thomas W. Geary; Jacqueline A. Atkins; George A. Perry; Emma M. Jinks; Michael F. Smith (Cell and Tissue Research, 2012)

Measurements of hillslope debris flow impact pressure on obstacles - Louis Bugnion; Brian W. McArdell; Perry Bartelt; Corinna Wendeler (Landslides, 2012)

Explaining fire‐driven landscape transformation during the Initial Burning Period of N ew Z ealand's prehistory - George L. W. Perry; Janet M. Wilmshurst; Matt S. McGlone; Dave B. McWethy; Cathy Whitlock (Global Change Biology, 2012)
At the time of M āori settlement, ca. 750 years ago, N ew Z ealand's ecosystems experienced catastrophic change, including the introduction of fire to ignition‐limited ecosystems and the resulting widespread loss of forest. While high‐resolution sediment‐charcoal analyses suggest this forest loss was rapid, M āori populations were small and transient during the Initial Burning Period and there is evidence for widespread fire activity in places where there is little archaeological evidence of human presence. These observations beg the question ‘how did small populations manage to transform large areas so rapidly?’ Using a simulation model, we demonstrate how the relationship between time since fire and flammability in N ew Z ealand's forests drives positive feedbacks that allow for rapid and extensive deforestation. Under ignition scenarios mirroring prehuman conditions, the model did not produce significant deforestation – thus, it is extremely unlikely that deforestation could have occurred without human‐initiated burning. Scenarios where ignition was spatio‐temporally random also failed to result in deforestation. Rapid and widespread forest loss occurred in scenarios incorporating spatio‐temporally savvy selection of ignition locations. Targeting ignitions in flammable vegetation was more important than targeting ignitions in years with favourable climatic conditions. However, targeting in space and time concurrently, such that flammable vegetation was ignited during favourable climatic years was the most efficient strategy of those simulated. Following the Initial Burning Period decadal ignitions would have been sufficient to maintain a deforested shrubland/grassland landscape. New Z ealand's Initial Burning Period is one of many that occurred across eastern Polynesia following human settlement, and these events have left long‐term legacy effects that remain evident in contemporary landscapes. Improving understanding of how humans shaped environments in N ew Z ealand in the past has implications for eastern P olynesia as a whole.

Dodo remains from an in situ context from Mare aux Songes, Mauritius - Hanneke J. M. Meijer; Arike Gill; Perry G. B. de Louw; Lars W. Van Den Hoek Ostende; Julian P. Hume; Kenneth F. Rijsdijk (The Science of Nature, 2012)

Two-Photon and Second Harmonic Microscopy in Clinical and Translational Cancer Research - Seth W. Perry; Ryan M. Burke; Edward B. Brown (Annals of Biomedical Engineering, 2012)

Does low-intensity surface fire increase water- and nutrient-availability to overstorey Eucalyptus gomphocephala? - Dugald C. Close; Neil J. Davidson; Perry W. Swanborough; Ross Corkrey (Plant and Soil, 2011)

Low-dimensional trade-offs fail to explain richness and structure in species-rich plant communities - Alexandra Esther; Jürgen Groeneveld; Neal J. Enright; Ben P. Miller; Byron B. Lamont; George L. W. Perry; Britta Tietjen; Florian Jeltsch (Theoretical Ecology, 2011)

Soil properties under different orchard floor management systems for organic apple production - Roberto J. Zoppolo; Dario Stefanelli; George W. Bird; Ronald L. Perry (Organic Agriculture, 2011)

Projected Reorganization of Florida Bay Seagrass Communities in Response to the Increased Freshwater Inflow of Everglades Restoration - Darrell Anthony Herbert; William B. Perry; Bernard J. Cosby; James W. Fourqurean (Estuaries and Coasts, 2011)

Effect of methamphetamine dependence on inhibitory deficits in a novel human open-field paradigm - Brook L. Henry; Arpi Minassian; Mandy van Rhenen; Jared W. Young; Mark A. Geyer; William Perry (Psychopharmacology, 2011)

Status and future of the forest health indicators program of the USA - Christopher William Woodall; Michael C. Amacher; William A. Bechtold; John W. Coulston; Sarah Jovan; Charles H. Perry; KaDonna C. Randolph; Beth K. Schulz; Gretchen C. Smith; Borys Tkacz; Susan Will-Wolf (Environmental Monitoring and Assessment, 2011)

A “Driving Force” in Developing the Nation's Forests: The McIntire-Stennis Cooperative Forestry Research Program - Steven H. Bullard; Perry J. Brown; Catalino A. Blanche; Richard W. Brinker; Don H. Thompson (Journal of Forestry, 2011)
The McIntire-Stennis (M-S) Cooperative Forestry Research Program has provided fundamental support for creating and strengthening forestry research and graduate training efforts at colleges and universities across the nation for nearly 50 years. M-S funding has helped produce thousands of forestry scientists and other research professionals, and M-S—supported research has provided critical basic understanding and applied solutions to extend the benefits that flow from forests and related rangelands across the nation over time. The 1962 legislation that created the M-S program authorized funding of up to one-half of the funds appropriated for federal forestry research conducted directly by the USDA. Throughout the program's history, however, M-S appropriations have been far below the authorized level. In 2012, the M-S program's 50th anniversary will be celebrated. Congress and the President therefore have a truly significant “golden anniversary” opportunity to strengthen the nation's investment in research and training that represents an essential and powerful “driving force behind progress” in sustaining forests for ecological, economic, and social benefits for present and future generations.

Width of riparian buffer and structure of adjacent plantations influence occupancy of conservation priority birds - Roger W. Perry; T. Bently Wigley; M. Anthony Melchiors; Ronald E. Thill; Philip A. Tappe; Darren A. Miller (Biodiversity and Conservation, 2011)

Regional differences in awareness and attitudes regarding genetic testing for disease risk and ancestry - Charles R. Jonassaint; Eunice R. Santos; Crystal M. Glover; Perry W. Payne; Grace-Ann Fasaye; Nefertiti Oji-Njideka; Stanley Hooker; Wenndy Hernandez; Morris W. Foster; Rick A. Kittles; Charmaine D. Royal (Human Genetics, 2010)

Polyphosphate in Trichodesmium from the low‐phosphorus Sargasso Sea - Elizabeth D. Orchard; Claudia R. Benitez-Nelson; Perry J. Pellechia; Michael W. Lomas; Sonya T. Dyhrman (Limnology and Oceanography, 2010)
Polyphosphate (polyP) is often considered to be the product of luxury uptake in areas of excess phosphorus (P), but can also accumulate in P‐depleted cells in response to P resupply. To test the hypothesis that polyP is present in phytoplankton from oligotrophic systems, the marine diazotroph Trichodesmium was collected from the low‐P surface waters of the Sargasso Sea and assayed with solid‐state 31 P nuclear magnetic resonance spectroscopy. Up to 25% of Trichodesmium cellular P was characterized as polyP, despite physiological data that indicated the colonies were P deplete. This was consistent with culture studies where there were high percentages of polyP under P‐deplete conditions. All Trichodesmium species examined had the genetic machinery to produce and degrade polyP. Trends in the amount of Trichodesmium polyP along the cruise transect showed that allocation of P to polyP was consistently high, and that the ratio of polyP : carbon varied with changes in temperature and mixed‐layer depth. It may be that Trichodesmium was taking advantage of pulses in P supply, and that polyP is a physiological fingerprint of this variability. Additionally, if polyP formation is a common trait in phytoplankton, polyP released from cells could be an additional bioavailable component of the dissolved organic P pool. Taken together, this study highlights the importance of polyP to P cycling and cellular P allocation even in oligotrophic regions.

Polyamines are required for the expression of key Hms proteins important for Yersinia pestis biofilm formation - Brian W. Wortham; Marcos A. Oliveira; Jacqueline D. Fetherston; Robert D. Perry (Environmental Microbiology, 2010)
Summary We previously showed that mutations in the genes encoding the two main biosynthetic enzymes responsible for polyamine production, arginine decarboxylase (SpeA) and ornithine decarboxylase (SpeC) cause a loss of biofilm formation in Yersinia pestis . In Y. pestis the development of a biofilm is dependent on 6 Hms (hemin storage) proteins (HmsH, F, R, S, T and P) grouped into 3 operons; hmsHFRS , hmsT and hmsP . In this article we show that polyamines are necessary to maintain the levels of key Hms proteins. In the absence of polyamines there is an ∼93%, ∼43% and ∼90% reduction in protein levels of HmsR, HmsS and HmsT respectively. Overexpression of hmsR and hmsT from plasmids alone can restore biofilm formation to a SpeA ‐ SpeC ‐ mutant. Addition of exogenous putrescine also restores normal levels of HmsR, HmsS, HmsT and biofilm production. Analyses using transcriptional reporters and quantitative RT‐PCR indicate that the initiation of transcription and mRNA stability are not reduced by polyamine deficiency. Instead, translational reporters indicate that polyamines function at least in part by modulating the translation of HmsR and HmsT. Although construction of a consensus Shine–Dalgarno sequence upstream of hmsT modestly reduced the stimulation of translation by putrescine, additional mechanisms likely contribute to the polyamine‐dependent expression of HmsT. Finally, we have shown that polyamines play a role in bubonic plague.

Assessing Potential Risk to Alligators, Alligator mississippiensis, from Nutria Control with Zinc Phosphide Rodenticide Baits - Gary W. Witmer; John D. Eisemann; Thomas M. Primus; Jeanette R. O’Hare; Kelly R. Perry; Ruth M. Elsey; Phillip L. Trosclair (Bulletin of Environmental Contamination and Toxicology, 2010)

Immobilizing nitrogen to control plant invasion - Laura G. Perry; Dana M. Blumenthal; Thomas A. Monaco; Mark W. Paschke; Edward F. Redente (Oecologia, 2010)

Primary Productivity in 20-year Old Created Wetlands in Southwestern Virginia - Robert B. Atkinson; James E. Perry; Gregory B. Noe; W. Lee Daniels; John Cairns (Wetlands, 2010)

GBR 12909 administration as a mouse model of bipolar disorder mania: mimicking quantitative assessment of manic behavior - Jared W. Young; Andrew K. L. Goey; Arpi Minassian; William Perry; Martin P. Paulus; Mark A. Geyer (Psychopharmacology, 2010)

p75 neurotrophin receptor regulates basal and fluoxetine-stimulated hippocampal neurogenesis - Michael J. Colditz; Vibeke S. Catts; Noura Al-menhali; Geoffrey W. Osborne; Perry F. Bartlett; Elizabeth J. Coulson (Experimental Brain Research, 2010)

Native cover crops suppress exotic annuals and favor native perennials in a greenhouse competition experiment - Laura G. Perry; Spencer A. Cronin; Mark W. Paschke (Plant Ecology, 2009)

Effects of 14 days of microgravity on fast hindlimb and diaphragm muscles of the rat - Mark D. Schuenke; David W. Reed; William J. Kraemer; Robert S. Staron; Jeff S. Volek; Wesley C. Hymer; Scott Gordon; L. Perry Koziris (European Journal of Applied Physiology, 2009)

Vulnerability of national economies to the impacts of climate change on fisheries - Edward H. Allison; Allison L. Perry; Marie‐Caroline Badjeck; W. Neil Adger; Katrina Brown; Declan Conway; Ashley S. Halls; Graham M. Pilling; John D. Reynolds; Neil L. Andrew; Nicholas K. Dulvy (Fish and Fisheries, 2009)
Anthropogenic global warming has significantly influenced physical and biological processes at global and regional scales. The observed and anticipated changes in global climate present significant opportunities and challenges for societies and economies. We compare the vulnerability of 132 national economies to potential climate change impacts on their capture fisheries using an indicator‐based approach. Countries in Central and Western Africa (e.g. Malawi, Guinea, Senegal, and Uganda), Peru and Colombia in north‐western South America, and four tropical Asian countries (Bangladesh, Cambodia, Pakistan, and Yemen) were identified as most vulnerable. This vulnerability was due to the combined effect of predicted warming, the relative importance of fisheries to national economies and diets, and limited societal capacity to adapt to potential impacts and opportunities. Many vulnerable countries were also among the world’s least developed countries whose inhabitants are among the world’s poorest and twice as reliant on fish, which provides 27% of dietary protein compared to 13% in less vulnerable countries. These countries also produce 20% of the world’s fish exports and are in greatest need of adaptation planning to maintain or enhance the contribution that fisheries can make to poverty reduction. Although the precise impacts and direction of climate‐driven change for particular fish stocks and fisheries are uncertain, our analysis suggests they are likely to lead to either increased economic hardship or missed opportunities for development in countries that depend upon fisheries but lack the capacity to adapt.

Combining remote sensing and economic analysis to support decisions that affect water productivity - P. J. G. J. Hellegers; R. Soppe; C. J. Perry; W. G. M. Bastiaanssen (Irrigation Science, 2009)

A consensus map of rye integrating mapping data from five mapping populations - J. Perry Gustafson; Xue-Feng Ma; Viktor Korzun; John W. Snape (Theoretical and Applied Genetics, 2009)

DNA-Protein Cross-Links in Erythrocytes of Freshwater Fish Exposed to Hexavalent Chromium or Divalent Nickel - Jim R. Kuykendall; Kyle L. Miller; Kristen M. Mellinger; Andrew J. Cain; Michael W. Perry; Michael Bradley; Eric J. Jarvi; Dennis J. Paustenbach (Archives of Environmental Contamination and Toxicology, 2009)

Filling the gap: improving estimates of working tree resources in agricultural landscapes - C. H. Perry; C. W. Woodall; G. C. Liknes; M. M. Schoeneberger (Agroforestry Systems, 2009)

Federated Access to Heterogeneous Information Resources in the Neuroscience Information Framework (NIF) - Amarnath Gupta; William Bug; Luis Marenco; Xufei Qian; Christopher Condit; Arun Rangarajan; Hans Michael Müller; Perry L. Miller; Brian Sanders; Jeffrey S. Grethe; Vadim Astakhov; Gordon Shepherd; et al. (Neuroinformatics, 2008)

Issues in the Design of a Pilot Concept-Based Query Interface for the Neuroinformatics Information Framework - Luis Marenco; Yuli Li; Maryann E. Martone; Paul W. Sternberg; Gordon M. Shepherd; Perry L. Miller (Neuroinformatics, 2008)

The Neuroscience Information Framework: A Data and Knowledge Environment for Neuroscience - Daniel Gardner; Huda Akil; Giorgio A. Ascoli; Douglas M. Bowden; William Bug; Duncan E. Donohue; David H. Goldberg; Bernice Grafstein; Jeffrey S. Grethe; Amarnath Gupta; Maryam Halavi; David N. Kennedy; et al. (Neuroinformatics, 2008)

Exposure to traffic emissions throughout life and risk of breast cancer - N. M. Perry; P. C. Allgood; S. W. Duffy; K. Mokbel (Cancer Causes & Control, 2008)

Concentrations of the Allelochemical (±)-Catechin IN Centaurea maculosa Soils - Laura G. Perry; Giles C. Thelen; Wendy M. Ridenour; Ragan M. Callaway; Mark W. Paschke; Jorge M. Vivanco (Journal of Chemical Ecology, 2007)

Vegetation dynamics in response to organic matter loading rates in a created freshwater wetland in southeastern Virginia - David E. Bailey; James E. Perry; W. Lee Daniels (Wetlands, 2007)

No evidence for root-mediated allelopathy in Centaurea solstitialis, a species in a commonly allelopathic genus - Bo Qin; Jennifer A. Lau; Joseph Kopshever; Ragan M. Callaway; Heather McGray; Laura G. Perry; Tiffany L. Weir; Mark W. Paschke; Jose L. Hierro; John Yoder; Jorge M. Vivanco; Sharon Strauss (Biological Invasions, 2007)

Regression Techniques for Examining Land Use/Cover Change: A Case Study of a Mediterranean Landscape - James D. A. Millington; George L. W. Perry; Raúl Romero-Calcerrada (Ecosystems, 2007)

In vivo pharmacological characterization of the structurally novel, potent, selective mGlu2/3 receptor agonist LY404039 in animal models of psychiatric disorders - Linda M. Rorick-Kehn; Bryan G. Johnson; Karen M. Knitowski; Craig R. Salhoff; Jeffrey M. Witkin; Kenneth W. Perry; Kelly I. Griffey; Joseph P. Tizzano; James A. Monn; David L. McKinzie; Darryle D. Schoepp (Psychopharmacology, 2007)

A comparison of methods for the statistical analysis of spatial point patterns in plant ecology - George L. W. Perry; Ben P. Miller; Neal J. Enright (Plant Ecology, 2006)

Marcy: A chipping variety with resistance to common scab and the golden nematode - Walter S. De Jong; Donald E. Halseth; Bill B. Brodie; Keith L. Perry; Joseph B. Sieczka; Barbara J. Christ; Gregory A. Porter; Ken M. Paddock; Michael W. Peck; Robert L. Plaisted (American Journal of Potato Research, 2006)

Zinc Toxicity Thresholds for Reclamation Forb Species - Mark W. Paschke; Laura G. Perry; Edward F. Redente (Water, Air, & Soil Pollution, 2006)

Adjunctive therapies for HIV-1 associated neurologic disease - Seth W. Perry; John P. Norman; Harris A. Gelbard (Neurotoxicity Research, 2005)

A new potato virus in a new lineage of picorna-like viruses - J. R. Thompson; K. L. Perry; W. De Jong (Archives of Virology, 2004)

Proclivity and effectiveness in gall defence by soldiers in five species of gall-inducing thrips: benefits of morphological caste dimorphism in two species (Kladothrips intermedius and K. habrus) - S. P. Perry; T. W. Chapman; M. P. Schwarz; B. J. Crespi (Behavioral Ecology and Sociobiology, 2004)

Analysis of Historical Salinity and Boron Surface Water Monitoring Data from the San Joaquin River Watershed: 1985–2002 - Lenwood W. Hall; William D. Killen; Ronald D. Anderson; Elgin Perry (Environmental Monitoring and Assessment, 2004)

?13C and water-use efficiency in Australian grasstrees and South African conifers over the last century - Perry W. Swanborough; Byron B. Lamont; Edmund C. February (Oecologia, 2003)

The Impact of Tick Control on the Productivity of Indigenous Cattle under Ranch Conditions in Uganda - J. Okello-Onen; E.M. Tukahirwa; B.D. Perry; G.J. Rowlands; S.N. Nagda; G. Musisi; E. Bode; R. Heinonen; W. Mwayi; J. Opuda-Asibo (Tropical Animal Health and Production, 2003)

Neuroscience data and tool sharing - Peter Eckersley; Gary F. Egan; Erik De Schutter; Tang Yiyuan; Mirko Novak; Vaclav Sebesta; Line Matthiessen; Irio P. Jaaskelainen; Ulla Ruotsalainen; Andreas V. M. Herz; Klaus-Peter Hoffmann; Raphael Ritz; et al. (Neuroinformatics, 2003)

Variation in propensity to defend by reproductive gall morphs in two species of gall-forming thrips - S. P. Perry; M. J. McLeish; M. P. Schwarz; A. H. Boyette; J. Zammit; T. W. Chapman (Insectes Sociaux, 2003)

Ontogenetic quinpirole treatments fail to prime for D2 agonist-enhancement of locomotor activity in 6-hydroxydopamine-lesioned rats - Ryszard Brus; Richard M. Kostrzewa; Preemyslaw Nowak; Ken W. Perry; John P. Kostrzewa (Neurotoxicity Research, 2003)

Humans, fire and landscape pattern: understanding a maquis‐forest complex, Mont Do, New Caledonia, using a spatial ‘state‐and‐transition’ model - George L. W. Perry; N. J. Enright (Journal of Biogeography, 2002)
Aim The research explores how changes in disturbance regime resulting from human settlement may affect landscape structure. A spatially explicit grid‐based simulation model is used to explore the interplay between humans, fire regime and landscape composition. Location The study site for this research is the botanical reserve at Mont Do, New Caledonia. The endemic conifer Araucaria laubenfelsii (Araucariaceae) forms a key component of the landscape at Mont Do. This species is unusual in that it is found scattered as an emergent in maquis and as a canopy species in adjacent rain forest patches. Although now dominated by a low maquis, prior to human settlement of New Caledonia, montane landscapes such as Mont Do are likely to have been heavily forested. Methods A spatially explicit simulation model, based on field data and palaeoecological information, was used to explore interactions between disturbance regime and the landscape. The model is described briefly here and more fully in Perry & Enright (2002) Ecological Modelling , 152 , 279. Results The model suggests that human‐influenced changes to the fire regime at Mont Do have been important in generating the current landscape structure. The origin and maintenance of forest landscapes and maquis‐forest mosaic landscapes are considered in the context of alternative stable states. Strong feedback loops between fire size and landscape composition, mediated at the smaller scale by other similar mechanisms, are capable of driving landscape change. The utility of a spatial state and transition modelling approach is demonstrated. Main conclusions The current landscape pattern on Mont Do is likely the result of changes to the fire regime occurring since human settlement. The specific mechanisms for this change outlined here may occur in a number of other similar systems. Understanding the origin and persistence of these ‘fire landscapes’ in New Caledonia and in the south‐west Pacific in general is crucial for their effective management.

Development of a Provisional Physical Habitat Index for Maryland Freshwater Streams - Lenwood W. Hall; Raymond P. Morgan; Elgin S. Perry; Anita Waltz (Environmental Monitoring and Assessment, 2002)

DIETS OF FIN, SEI, AND SPERM WHALES IN BRITISH COLUMBIA: AN ANALYSIS OF COMMERCIAL WHALING RECORDS, 1963–1967 - Rowenna D. Flinn; Andrew W. Trites; Edward J. Gregr; R. Ian Perry (Marine Mammal Science, 2002)
A bstract Diets of fin ( Balaenoptera physalus ), sei ( Balaenoptera borealis ), and sperm whales ( Physeter macrocephalus ) were estimated from the stomach contents of individuals killed along the British Columbia coast from 1963 to 1967. The dominant prey types of fin whales were euphausiids, with minor contributions from copepods and fish. Sei whale stomachs contained primarily copepods in three years, whereas euphausiids or a variety of fish dominated the diet in the other two years. Sperm whales consumed primarily North Pacific giant squid ( Moroteuthis robusta ), but secondary prey differed between males and females. Female sperm whales frequently consumed ragfish ( Icosteus spp.) and other fish, whereas the male diet also contained rockfish ( Sebastes spp.). The high abundance of euphausiids along the British Columbia coast likely contributed to the presence of a summer resident population of fin whales. The high abundance of large copepods farther north probably influenced the migration of sei whales through the offshore waters of British Columbia. Sperm whale stomach contents differed by sex reflecting location and possibly breeding behaviors.

Fluoxetine, but not other selective serotonin uptake inhibitors, increases norepinephrine and dopamine extracellular levels in prefrontal cortex - Frank P. Bymaster; Wei Zhang; Petra A. Carter; Janice Shaw; Eyassu Chernet; Lee Phebus; David T. Wong; Kenneth W. Perry (Psychopharmacology, 2002)

Tumor Necrosis Factor-Alpha in Normal and Diseased Brain: Conflicting Effects Via Intraneuronal Receptor Crosstalk? - Seth W Perry; Stephen Dewhurst; Matthew J Bellizzi; Harris A Gelbard (Journal of NeuroVirology, 2002)

Diapause in copepods (Crustacea) from ephemeral habitats with different hydroperiods in Everglades National Park (Florida, U.S.A.) - Maria Cristina Bruno; William F. Loftus; Janet W. Reid; Sue A. Perry (Hydrobiologia, 2001)

Developing jellyfish strategy hypotheses using circulation models - Donald R. Johnson; Harriet M. Perry; W. David Burke (Hydrobiologia, 2001)

DNA sequence analysis identifies genetically distinguishable populations of harp seals ( Pagophilus groenlandicus ) in the Northwest and Northeast Atlantic - E. A. Perry; G. B. Stenson; S. E. Bartlett; W. S. Davidson; S. M. Carr (Marine Biology, 2000)

Activation of the mesocorticolimbic dopaminergic system by stimulation of muscarinic cholinergic receptors in the ventral tegmental area - B. Gronier; K. W. Perry; K. Rasmussen (Psychopharmacology, 2000)

Sex differences in sensorimotor gating of the human startle reflex: all smoke? - N. R. Swerdlow; M. A. Geyer; P. L. Hartman; J. Sprock; P. P. Auerbach; K. Cadenhead; W. Perry; D. L. Braff (Psychopharmacology, 1999)

Biologically active compounds from Ozothamnus leptophyllus - Jacqueline E. Wood; Murray H. G. Munro; John W. Blunt; Nigel B. Perry; John R.L. Walker; Josephine M. Ward (New Zealand Journal of Botany, 1999)
A crude extract from a New Zealand native plant, Ozothamnus leptophyllus , was shown to possess antifungal activity. Flavonoids, mainly chalcones in the leaf exudate, were isolated, some of which possessed antiviral as well as antifungal activity. These flavanoids are excreted by glandular trichomes and form quasi‐crystalline deposits on the abaxial side of the leaves. 2’,4’,6'‐Trihydroxy‐chalcone was found to be active against both Polio virus (Pfizer vaccine strain) and Herpes simplex type 1 (ATCC VR 733); it was also responsible for anti‐dermatophytic activity against Trichophyton mentagrophytes . 2’,4'‐Dihydroxy‐4'‐methoxy‐dihydrochalcone was also active against both viruses.

Population dynamics of ticks on indigenous cattle in a pastoral dry to semi-arid rangeland zone of Uganda - J. Okello-Onen; E.M. Tukahirwa; B.D. Perry; G.J. Rowlands; S.M. Nagda; G. Musisi; E. Bode; R. Heinonen; W. Mwayi; J. Opuda-Asibo (Experimental and Applied Acarology, 1999)

Distributions of the vectors of heartwater, Amblyomma hebraeum and Amblyomma variegatum (Acari: Ixodidae), in Zimbabwe - T.F. Peter; B.D. Perry; C.J. O'Callaghan; G.F. Medley; W. Shumba; W. Madzima; M.J. Burridge; S.M. Mahan (Experimental and Applied Acarology, 1998)

Analyzing maps of dispersal around a single focus - S. Korie; S.J Clark; J.N Perry; M. A. Mugglestone; P .W. Bartlett; E. J . P. Marshall; J. A. Mann (Environmental and Ecological Statistics, 1998)

Olanzapine increases in vivo dopamine and norepinephrine release in rat prefrontal cortex, nucleus accumbens and striatum - Xi-Ming Li; Kenneth W. Perry; David T. Wong; F. P. Bymaster (Psychopharmacology, 1998)

GENETIC AND BEHAVIORAL EVIDENCE THAT HARBOR SEAL ( PHOCA VITULINA ) FEMALES MAY MATE WITH MULTIPLE MALES - E. A. Perry; W. Amos (Marine Mammal Science, 1998)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

The effects of hypercapnia on branchial and renal calcium fluxes in the rainbow trout ( Oncorhynchus mykiss ) - W. M. MacKenzie; S. F. Perry (Journal of Comparative Physiology B, 1997)

Earthquake Planning for Government Continuity - RONALD W. PERRY (Environmental Management, 1997)

Changes in mutagenicity during crude oil degradation by fungi - Linda E. Rudd; Jerome J. Perry; Virginia S. Houk; Ron W. Williams; Larry D. Claxton (Biodegradation, 1996)

Co-metabolism as a factor in microbial degradation of cycloparaffinic hydrocarbons - H. W. Beam; J. J. Perry (Archives of Microbiology, 1973)

A plaque assay system for rinderpest virus and its use in characterising virus adsorption - W. P. Taylor; C. T. Perry (Archives of Virology, 1970)

Experimental infection of the argasid tick, ornithodoros moubata porcinus, with African swine fever virus - W. Plowright; C. T. Perry; M. A. Peirce; J. Parker (Archives of Virology, 1970)

A potato breeding technique used for Texas - Bruce A. Perry; Robert V. Akeley; W. B. Cook (American Journal of Potato Research, 1960)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)